THE CLINICAL EFFECT OF ORAL VITAMIN D₃ SUPPLEMENTATION ON PSORIASIS PATIENTS ATTENDING OUTPATIENT TERTIARY CARE CENTRE - Dr Surendra Singh Bhati; Dr Ujjwal Jharia; Dr Shelly Yadav; Dr Ayush Yadav (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Psoriasis is a chronic immune-mediated inflammatory skin disease characterized by hyperproliferation of keratinocytes and dysregulated immune responses. Emerging evidence suggests a link between vitamin D deficiency and increased disease severity in psoriasis due to its role in epidermal homeostasis and immune modulation. However, the therapeutic efficacy of oral vitamin D₃ supplementation in Indian patients with chronic plaque-type psoriasis remains underexplored. The present study aimed to evaluate the clinical efficacy and safety of oral vitamin D₃ supplementation in patients with chronic plaque psoriasis and low baseline serum vitamin D levels.Methods: This prospective interventional study included 100 adult patients with chronic plaque-type psoriasis and documented serum 25(OH)D levels